Membangun Budaya Kerja Yang Mendukung Kinerja Tinggi - Dedi Rianto Rahadi; Alfina Nandaika; Anisa Noviyanti; Muhamad Rakhan Kusumardani; Zaky Saputra (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to explain the role of organizational culture in enhancing employee performance in a company. A qualitative approach with a literature review is used as the research methodology, while data collection techniques are conducted through documentary studies. The collected data is then processed through the process of reduction, presentation, and conclusion drawing. The research findings indicate that organizational culture is formed from the implementation of values, norms, and policies by organizational leaders, while employee performance is measured based on their work results in completing organizational tasks. The role of organizational culture in improving employee performance includes aspects of innovation, attention to detail, benefit orientation, individual orientation, team orientation, aggressiveness, and job stability. This is beneficial in shaping work habits that align with the standards set by the organization; therefore, leaders need to propose ideas or policies that can shape the desired work culture.